Teaching Tactics and Teacher Quality - Swaminatha Pillai, S. (Journal of Engineering Education Transformations, 1996)
What is Teaching? Teaching is an act of three elements, teacher, student and subject, which interrelate in an environment at a give n time, thus establishing itself as apentadic relationship. Teaching relationship is very dynamic and so constantly changing. Learning style refers to the actions and not the ability of students and hence is broad e r than cognitive achievement.